MARKET RESEARCH OF CARE GOODS FOR NEWBORNS AND FIRST YEAR CHILDREN - A. I. Ovod; S. I. Banin (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Comparative results of marketing research of care goods for newborns and first year children conducted in 2009 and 2014 showed that there were changes in the range of products and consumer preferences. The analysis revealed that the economic situation affected the determinants of choice in this category of goods and the location of purchasing. The findings should be considered by pharmaceutical companies in their procurement in order to improve their competitive position.